The Effect of Using Quizizz Educational Game Media for Increasing Class IV Students' Learning Motivation in Social Science - ., Nasaruddin; Pada, Amir; ., Elpisah (KnE Social Sciences, 2024)
The problem in this study is the lack of use of the educational game media Quizizz which causes a lack of student motivation in social studies learning. The purpose of this research is: (1) to describe the use of educational game media Quizizz in social studies subjects, (2) to describe students’ learning motivation after using Quizizz educational game media, and (3) to find out whether there is a significant effect after using Quizizz educational game media. This study uses a quantitative approach to the type of experimental research. The type of experiment chosen was pre-experimental research with data collection instruments in the form of tests, observations, and questionnaires. The data analysis technique used is descriptive analysis and inferential analysis. Data was collected through a learning motivation questionnaire. The results of this study indicate that the implementation of the learning process using the media educational game Quizizz affects student motivation. Keywords: student learning motivation, games, quizizz